Association of Adult Atopic Dermatitis with Impaired Oral Health and Oral Dysbiosis: A Case-Control Study - Aaya Shahin; Yael Anne Leshem; Yossi Taieb; Sharon Baum; Aviv Barzilai; Danielle Jeddah; Efrat Sharon; Omry Koren; Rinat Tzach-Nahman; Shunit Coppenhagen-Glazer; Ronen Hazan; Yael Houri-Haddad; et al. (International Dental Journal)
Background: Systemic alterations in the oral cavity can be reflected in skin disorders like psoriasis. However, data about oral health factors that are affected and controlled mainly by oral microbiota in atopic dermatitis (AD) are sparse. This study compared the oral status and oral microbiota of AD patients and healthy controls. Methods: This was a prospective sex- and age-matched case-control study comparing adult participants with and without dermatologist-verified AD. A dentist assessed oral health status, and oral flora samples were collected and subjected to 16S rRNA sequencing for microbiome analysis. Results: Forty-five AD participants and 41 non-AD controls were recruited. Compared to the participants in the control group, those with AD had significantly higher plaque levels (P = .04), poorer oral hygiene indices (P = .04), and higher gingival index trends (P = .05). The oral microbiome in the AD group showed significantly higher diversity, both in α and β diversities (P = .001, P = .0007, respectively). Furthermore, AD patients had a significantly increased abundance of taxa correlated with oral diseases and a decreased abundance of bacteria associated with a healthy oral status. Conclusion: AD appears to be associated with poor oral health and oral dysbiosis. There is a need to increase both patients’ and physicians’ awareness of oral health.